Ideological Foundations and Problems: Comparative Analysis of Character Education in Singapore and Indonesia - Huwaida, Jaziela; Ahmadan, Madani; Syarifah, Syarifah; Anwar, Saiful (LP. Ma'arif Janggan Magetan, 2024)
This study compares Singapore and Indonesia's approaches to character education. The three main subjects of this study are the problems and ideological foundations of character education in the two countries. A qualitative research method with a library approach, often referred to as desk research, is the methodology used. Study findings, published works, or official policies related to character education in the two countries are the sources of the data. Character education in Indonesia is based on the country's ideology, culture, religious views and customs, according to the research findings. Similarly, government policy constraints, official ideologies and philosophical beliefs form the foundation of character education in Singapore. Singapore and Indonesia both have problems with free sex, vandalism, thuggery and juvenile crime. Variations in stress levels affect the character of young people due to the high level of mobility in Singapore.